Optimization of Generator Set (Genset) Capacity to Supply Electrical Load For Palm Harvesters’ Barracks In Marike - Rouna Zinggibey Tito; Dino Erivianto; Rahmaniar, Rahmaniar (Sean Institute, 2025)
Good management of electrical loads from distribution substations will greatly affect the performance and reliability as well as continuity of installed load services. Related components include transformer capacity, conductors, safety devices, and so on. backup power supply source in case of blackout from PLN, then the harvester barracks in Marike have a standby generator. This generator is expected to be able to supply the electrical load in the palm oil harvester barracks area during the transfer from the main power source/PLN to the backup power source/generator. When PLN goes out, the generator will supply the load in the palm oil harvester barracks area of 65,000 Watts.The maximum load installed in each Harvester barracks in Marike reaches 2200 watts for 1 barrack, while the Harvester barracks in Marike have 17 barracks, so the total installed load reaches 2200 x 17 = 37,400 Watts. The total load installed as street lighting and the Harvester barracks area in Marike is = 2700 watts. The total load installed on Palm Oil Harvesters Barracks In Marikeis 50,125 VA. Maximum load + 20%. Generator capacity= 50,125 VA + (20% x 50,125VA) = 50,125 VA+ 10,025 VA = 60,150 VA (65 kVA). So it is calculated as 171.05A : 3 (Core) = 57.01A. So the protection used is worth 57 A. The size of the conductor with a current value of 57.01 A, then the diameter of the conductor needed is a NYY 35 mm2 conductor.